Hear Our Collective Voices! Mother Survivors and Activist Movement to End Violence Against Women with Children - Breton, Pat; Kratochvil, Eva; Lang, Paula (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
This article examines the experiences of women with children fleeing violence and survivor-activists in Ontario. Mothers are speaking out about systemic barriers and diminishing state support for women and their children fleeing violence within state systems responsible for protecting them. Lack of safe, affordable housing and universal child care supports and policing and child welfare interventions that fail to support women and their children’s safety are most harshly realized by Indigenous, racialized, and low-income women with children seeking violence-free lives (Cull; Mann; Greaves et al.; Sinclair). Our aim is to shed light on state systems failing women with children fleeing violence; state policies retrenching race, gender, and class inequalities; and alternative accountability models for survivor-activists organizing to address systemic oppression. We argue that survivor activism in Ontario is crucial both within and outside the state to drive fundamental change and state accountability for violence against women at community and provincial levels.